ANALISIS PERENCANAAN PERAWATAN SPINDLE MOULDER DENGAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) DI PT. ROMI VIOLETA - Muhammad Ardian Firmansyah; Ahmad Syuhri (ROTOR, 2022)
In a furniture company, there are several production machines that are used and in the process are interconnected. The production machines used often experience downtime or machine failure. One of which is the spindle moulder machine, it is a cutting machine used to cut wood with various profiles as needed. Damage to this machine can cause the production process to stop, so that downtime will increase and the production target that has been set will be reduced. To maintain the working condition of the machine so that it can last a long time and run optimally, the initial step is in the form of scheduling maintenance. RCM is a strategy to optimize the company's asset maintenance program so that it can operate effectively. This research method uses quantitative analysis conducted on the spindle moulder machine and qualitative analysis includes FMEA and RCM II Decision Worksheet which will be used as references to identify component failures and determine appropriate maintenance actions. The research results, the availability value for the spindle bearing component is 99.72%, the motor component is 99.78%, and the v belt component is 99.77%, so the average availability value is 99.76%. The value of downtime after preventive maintenance using the RCM method on the spindle moulder machine is 43.54 hours with a decrease in machine downtime of 30.96 hours (41.55%).